Behavioral and neural auditory thresholds in a frog. Issue 3 (6th December 2018) - Taylor, Ryan C; Akre, Karin; Wilczynski, Walter; Ryan, Michael J
Abstract: Vocalizations play a critical role in mate recognition and mate choice in a number of taxa, especially, but not limited to, orthopterans, frogs, and birds. But receivers can only recognize and prefer sounds that they can hear. Thus a fundamental question linking neurobiology and sexual selection asks—what is the threshold for detecting acoustic sexual displays? In this study, we use 3 methods to assess such thresholds in túngara frogs: behavioral responses, auditory brainstem responses, and multiunit electrophysiological recordings from the midbrain. We show that thresholds are lowest for multiunit recordings (ca. 45 dB SPL), and then for behavioral responses (ca. 61 dB SPL), with auditory brainstem responses exhibiting the highest thresholds (ca. 71 dB SPL). We discuss why these estimates differ and why, as with other studies, it is unlikely that they should be the same. Although all of these studies estimate thresholds they are not measuring the same thresholds; behavioral thresholds are based on signal salience whereas the 2 neural assays estimate physiological thresholds. All 3 estimates, however, make it clear that to have an appreciation for detection and salience of acoustic signals we must listen to those signals through the ears of the receivers.